Art of Choosing: The Decisions We Make Everyday - Sheena Iyengar (USA Abacus, 2011)
Every day we make choices. Whether mundane or life-altering, these choices define us and shape our lives. Sheena Iyengar asks the difficult questions about how and why we choose and her research reveals surprising and profound answers.
Keywords: Business; Nonfiction; Psychology; Self Help; Science; Agile Management (HRM2072-N)